Cystic Echinococcosis in the Liver: Nomenclature and Surgical Procedures - António Menezes da Silva (Journal of Surgery and Surgical Research - Peertechz Publications, 2015)
Cystic Echinococcosis (CE) is a zoonotic infection caused by larval form of the parasite Echinococcus granulosus. The adult tapeworm inhabit the small intestine of some carnivores (called definitive or final hosts), and the larval phase, or "metacestode" develops in the herbivores (intermediate hosts). The presentation form of the larval phase is the development of cysts, called hydatid cysts. Although all of us know the vital cycle of the parasite and the different aspects of the disease, the designations around the parasite, its evolution and some therapeutic procedures is not uniform. In fact we frequently see the use of inappropriate terms, based on incorrect concepts. It would be useful to use the same nomenclature and it is absolutely necessary that the nomenclature is correct and universally accepted. So, it is pertinent to remember some important points related to the CE and, above all, to clarify some aspects concerning its nomenclature, in order to understand better the therapeutic options, particularly the different surgical approaches. Despite the cysts can be localized in any organ, liver localization is the most frequent (60-70%). The development of a hydatid cyst is slow and usually without specific clinical manifestations, so the diversity of clinical manifestations is related to the anatomical localization of the cyst, its dimension, and the antigens responsible for the systemic hypersensitivity, which can occur in sequence of cyst rupture, spontaneously or traumatic, resulting in secondary echinococcosis. The therapeutic approach has nowadays different possibilities, which will be referred in this manuscript.